Ameliorating Child poverty through Connecting Economic Services with child health Services (ACCESS): study protocol for a randomised controlled trial of the healthier wealthier families model in Sweden - Nina Johansson; Anna Sarkadi; Inna Feldman; Anna M. H. Price; Sharon Goldfeld; Tapio Salonen; Katarina Wijk; David Isaksson; Emir Kolic; Sara Stenquist; Maria Elg; Ewa Lönn; et al. (BMC, 2022)
Abstract Background Sweden is often held up as an example of a country with low child deprivation; yet, rates of relative deprivation are rising. Every municipality in Sweden is required to provide free, timely and accessible budget and debt counselling under the Social Services Act. The services have been encouraged to perform preventative practice with families; however, this has not been realised. The Healthier Wealthier Families (HWF) model embeds universal screening for economic hardship into child health services and creates a referral pathway to economic support services. Given the universal child health system in Sweden, which is freely available and has excellent coverage of the child population, implementation of the HWF model has potential to support families to access the freely available municipal budget and debt counselling and ultimately improve rates of child deprivation in Sweden. Methods/design We will conduct a two-arm randomised waitlist-control superiority trial to examine the effectiveness and cost-effectiveness of the HWF model in the Sweden. A longitudinal follow-up with the cohort will explore whether any effects are maintained in the longer-term. Discussion HWF is a collaborative and sustainable model that could maximise the effectiveness of current services to address child deprivation in Sweden. The study outlined in this protocol is the first effectiveness evaluation of the HWF model in Sweden and is a crucial step before HWF can be recommended for national implementation within the child health services. Trial registration Clinicaltrials.gov; NCT05511961. Prospectively registered on 23 August 2022. https://clinicaltrials.gov/ct2/show/NCT05511961